The future security environment in the Middle East : conflict, stability, and political change - Bensahel, Nora, 1971-; Byman, Daniel, 1967- (RAND/Project Air Force, 2004)
The security environment in the Middle East has become increasingly complicated during the past decade. This report identifies several important trends that are shaping regional security and identifies their implications for the United States. Many traditional security concerns, such as energy security and the proliferation of weapons of mass destruction, will remain significant factors in the future. However, ongoing domestic changes throughout the region will become increasingly important as well. Issues such as political reform, economic reform, civil-military relations, leadership change, and the information revolution are all affecting regional security dynamics. This report examines each of these issue areas and identifies some of the challenges that they pose for U.S. foreign policy.